Investigating the Methods of Restaurant Rating to Develop Halal Compliance Rating (HCR) Tool Within the Halal Certified Restaurants Globally - Md Siddique E Azam; Moha Asri Abdullah; Anis Najiha Ahmad (Universitas Muhammadiyah Yogyakarta, 2022)
This paper reviews the weighted average approach of rating systems among the restaurant industries globally. Such review is crucial to developing Halal Compliance Rating (HCR) tool within the halal-certified restaurants in Malaysia as all as in other parts of the world. Halal-certified restaurants are in the Halal food and beverage (F&B) industry. At this moment, the Halal F&B industry does not have any standard rating method to rate the level of halal compliance practice of halal-certified restaurants. Hence, the objective of the study is to investigate the methods of restaurant rating globally and adopt the best-suited method to develop an HCR tool within halal-certified restaurants. Simultaneously, the study finds and recommends suitable linguistic and symbolic expressions for different ratings of halal compliance. To achieve the objectives, an extensive literature review was carried out. Additionally, to develop the HCR tool, the study used the ten components of halal compliance identified and weighted by Azam (2021). The findings show an example of using and calculating the HCR tool to rate the halal compliance of a restaurant and expressing the ratings linguistically and/or symbolically. Simultaneously, this paper justifies the use of the weighted average approach for rating halal-certified restaurants. Finally, it provides recommendations for future research to establish a standard HCR tool globally.